Diagnostic Analysis of mZN Microscopy and PCR for Detection of Cryptosporidiosis in Goat Kids – A Molecular Epidemiological Study - Atul Kumar Sharma; K. Gururaj; Anjana Goel; Rama Sharma; Souvik Paul; Dinesh Kumar Sharma (The Indian Veterinary Journal, 2024)
The occurrence of Cryptosporidium species infection and its risk factors in neonatal goats is less explored. Also it is due to the fact that diseases like colibacillosis and neonatal viral enteritis complex caused by Group A rotaviruses and Bovine corona viruses can co-exist with Cryptosporidium and can lead to mixed infections and the latter is often overlooked. Therefore, in the current research we explored the cryptosporidial occurrence in neonatal goats of Mathura district of Uttar Pradesh, India. In this study, a total of 644 faecal samples were collected from neonatal goats at different villages and certain organized farms of Mathura district age-wise, season-wise and breed-wise, and were examined for Cryptosporidium based on modified Ziehl-Neelsen technique, conventional 18SSU rRNA nested PCR assay. The overall prevalence of Cryptosporidium infection in goats based on microscopy was 36.80% (237/644; p value